Agricultural permanence in large Asian cities: a case study of Nanjing, China. Issue 1 (2nd January 2021) - Veeck, Gregory; Emerson, Charles; Breidinger, Erik S.
ABSTRACT: Nanjing, the capital of China's Jiangsu Province, has grown rapidly during the post-reform era and the pace of change placed tremendous pressure on the city's arable land resources. This case study of land use/land cover change (LU/LC) in Nanjing's Jiangning district assesses changes in agricultural land, production, and labor within the ten 2016-era jiedao (sub-district political units) of Jiangning from 2000 to 2015. This case study provides an opportunity to assess an important component of the Ginsburg-McGee desakota hypothesis predicting that Asian extended metropolis regions, unlike similar large cities in Western nations, will consistently maintain agricultural land and labor supplies within metropolitan boundaries. The study is based on field visits combined with time-series LU/LC analyses of a GIS database joining archived agricultural and agro-economic data with additional LU/LC data layers derived from satellite imagery including Landsat 8 Operational Land Imager (OLI) and Landsat 5 Thematic Mapper (TM) imagery. Results show Jiangning continues to retain high, if decreasing, proportions of agricultural land and employment. After significant decreases for all ten jiedao from 2000 to 2010, government policies appear to have helped stabilize arable land losses from 2010 to 2015. Jiedao in the closest proximity to Nanjing's central business districts lost arable land at greater rates than those in the periphery. OLS linear multiple regression analyses identified factors that are the most effective predictors of arable land persistence including lower mean annual income, higher percentage of men in the farm workforce, higher reliance on traditional double-cropped rice-wheat, and less vegetable production.